The everyday-life in neanderthal times: a full-immersive Pleistocene reconstruction for the Casal De' Pazzi Museum (Rome) - Augusto Palombini; Antonia Arnoldus-Huyzendveld; Marco Di Ioia; Patrizia Gioia; Carlo Persiani; Sofia Pescarin (Virtual Archaeology Review)
The Museum of Casal De' Pazzi (Rome) is built since about ten years on a Pleistocene floor consisting in the ancient riverbed of the Aniene river, at about 200.000 bp. Since its opening, it has been characterized by a strong narrative approach, and communication effort. The digital project realized by the Italian CNR (Institut for Technology applied to Cultural Heritage) implies three applications: a flood simulation, to show the water refilling of the ancient riverbed; a movie in computer-graphic, to be shown to the public, explaining neanderthal man and ancient elephant's life, and an edu-game, for children's learning, the Plei-stostation, implemented by touch-screen interaction dynamics.